The Influence of Book Creators on the Literacy and Numeracy Skills of Children Aged 5-6 Years - Ii Hartati; Asep Kurnia Jayadinata; Ii Hartati; Asep Kurnia Jayadinata (Universitas Negeri Malang, 2026)
This study aims to determine the effect of the use of Book Creator digital media on the literacy and numeracy skills of children aged 5–6 years. The study used a quasi-experimental method with a pretest-posttest nonequivalent control group design. The study subjects consisted of 30 children who were divided into an experimental group (n=15) and a control group (n=15). The experimental group learned using the Book Creator